Dual diagnosis at the neuro-immune interface: a case report of neuronal intranuclear inclusion disease with acute anti-CASPR2 encephalitis - Zhu, Wan; Liu, Tiansi; Yu, Xinran; Peng, Min; Hu, Jinghan (Frontiers in Immunology, 2025)
Neuronal intranuclear inclusion disease (NIID) is a rare autosomal-dominant, progressive neurodegenerative condition characterized by complex and variable clinical manifestations that can affect multiple neurological domains. This report describes the case of a 49-year-old female patient with a 10-year history of headaches, whose older sister had been diagnosed with NIID 1 year earlier through genetic testing and a skin biopsy. Recently, the patient developed dizziness and vomiting. Although symptomatic treatment reduced incidents of vomiting, her dizziness progressively worsened. It was accompanied by lower limb weakness, gait instability, hallucinations, and abnormal sleep behaviors. Routine imaging and cerebrospinal fluid immunological and microbiological tests revealed no abnormalities. Genetic analysis revealed a 130-repeat expansion in the NOTCH2NLC gene, and skin biopsy confirmed the presence of intranuclear inclusions, establishing the NIID diagnosis. However, during hospitalization, the patient’s bilateral lower limb tremors, hallucinations, and abnormal sleep behaviors suggested a possible acute encephalitic process. Subsequent serum testing detected positive anti-contactin-associated protein-like 2 (CASPR2) antibodies. Significant symptom improvement following treatment with immunoglobulins and steroids supported the diagnosis of coexisting acute anti-CASPR2 antibody encephalitis and NIID. This is the first reported case of dual disease coexistence.